Model Komunikasi di Sekolah Alam (Studi Kasus Model Komunikasi antara Guru dengan Murid di SMP IT Alam Nurul Islam Yogyakarta) - , NABILLA KUSUMA V; , Dian Aryami, SIP., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In 2012, Indonesia was ranked the lowest serving education system in the world. One of the reasons was the application of the âbankingâ education system where teachers have the epistemological authority in this system while students' pre-existing knowledge is ignored. The implementation of this system forms linear communication from teachers to students with no discussion opportunities available in class. In Yogyakarta, there is a school that moves away from the âbankingâ system and uses ânatureâ method where students are considered both active objects and subjects at the same time. This school, SMP IT Alam Nurul Islam Yogyakarta, invites their students to study through nature, research, and independent findings. The communication models in the school vary from linear to transactional.